Higher variety and quantity of microRNA‐139‐5p isoforms confer suppressive role in hepatocellular carcinoma. Issue 8 (25th April 2018) - Ni, Hengli; Dai, Xiaoxiao; Leng, Xueqin; Deng, Min; Qin, Yan; Ji, Qinghua; Xu, Chunfang; Li, Jianming; Liu, Yao
Abstract: MiRNA isoforms (isomiRs) were defined as an addition or deletion of one or more nucleotides at the 5′ or 3′ ends or both. Different isomiRs of the same miRNA can target different genes, which have extended the regulatory scale medicated by miRNA. In this study, we systematically analyzed miRNA isoforms in hepatocellular carcinoma (HCC) based on The Cancer Genome Atlas (TCGA) data and further explore their role by in silico and in vitro studies. We found that higher variety and quantity of miR‐139‐5p isoforms negatively correlated with the malignancy of HCC. And patients with higher variety and quantity of iso‐miR‐139‐5p exhibited favorable survival, independent of tumor stage. Interestingly, miR‐139‐5p ‐1|‐1 showed increased complementary effect of its target IGF1R than the archetype of miR‐139‐5p, and could further inhibit cellular movement more vigorously than its archetype. In conclusion, not only miR‐139‐5p itself, but its isoforms' variety and quantity confer suppressive role in HCC. Abstract : The novel findings in this study is that not only miR‐139‐5p itself, but also its isoforms' variety and quantity confer suppressive role in HCC.